2019
DOI: 10.1109/access.2019.2901568
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Neural Networks for WCE Abnormality Detection: CNN Architecture, Region Proposal and Transfer Learning

Abstract: Wireless capsule endoscopy (WCE) plays an important role in the diagnosis of gastrointestinal diseases. However, it is very time-consuming and fatiguing for a physician to review a large number of WCE images. Some methods to address this problem have recently been presented. However, these methods generally employ classification algorithms to discriminate abnormal from normal images, which do not localize, recognize, or detect abnormal patterns in abnormal images. We sought to identify a better method for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…The results showed that according to tumor motion and projection angles which exhibits that the CNN based method was more robust and accurate in real-time tumor localization [48]. Lan et al (2019) explored that multiregional combination such as selective search, edge boxes, and abjectness is used to improve object localization that account as essential of the non-rigid and amorphous characteristics to improve object localization [41]. Urban et al (2018) showed ADR aim of colonoscopy and accuracy according of colonoscopies for ADR.…”
Section: Medical Image Localizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that according to tumor motion and projection angles which exhibits that the CNN based method was more robust and accurate in real-time tumor localization [48]. Lan et al (2019) explored that multiregional combination such as selective search, edge boxes, and abjectness is used to improve object localization that account as essential of the non-rigid and amorphous characteristics to improve object localization [41]. Urban et al (2018) showed ADR aim of colonoscopy and accuracy according of colonoscopies for ADR.…”
Section: Medical Image Localizationmentioning
confidence: 99%
“…It is a type of advanced optical fluorescence technology which undergoing application assessments in brain tumor surgery while most of the images distorted and interpreted as non-diagnostic images [40]. In gastrointestinal diseases, new medical imaging technique innovated which known as wireless capsule endoscopy (WCE) to record WCE frame images to detect abnormal patterns [41]. It uses to diagnose of gastrointestinal diseases through a sensor which is quite small to swallow and capture every scenes of anatomical parts that pass through them [41].…”
Section: Medical Image Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, though CNN has great potential for the detection of mucosal breaks in WCE images, in some cases, the handcrafted machine learning approaches may perform better than CNN algorithms. To address the problem of small WCE dataset, Lan et al [31] proposed a deep cascade network architecture (CascadeProposal) pre‐trained via transfer learning (fine‐tuning) only for bleeding, polyp and tumours recognition from WCE images. Ulcer detection from WCE images is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%